DFT and dynamic analysis of glucose alcoholysis conversion to 5-ethoxymethylfurfural and ethyl levulinate. (15th October 2022) - Wang, Shijie; Chen, Yihang; Jia, Yu; Wang, Chen; Xu, Guizhuan; Jiao, Youzhou; He, Chao; Chang, Chun; Guo, Qianhui
Graphical abstract: Highlights: Efficient conversion of glucose to EMF catalyzed by USY in ethanol/THF was developed. The macroscopic reaction kinetic study indicated that THF can protect EMF from easy degradation to EL. Al 3+ is the preferred Lewis acid site on USY for catalyzing glucose conversion to EMF. DFT calculations showed that THF can reduce the energy barrier of USY-catalyzed glucose isomerization. THF increased the LUMO energy of EMF, which decreased its susceptibility to nucleophilic attack and reduced the adverse alcoholysis of EMF and humins production. Abstract: An effective catalytic strategy for the conversion of glucose to 5-ethoxymethylfurfural (EMF) catalyzed by ultrastable Y zeolite (USY) in a co-solvent system was developed. Effects of co-solvent and reaction conditions were first investigated. Tetrahydrofuran (THF) with low dipolarity/polarizability (π*) was screened as the appropriate co-solvent, and a higher EMF yield of 41.46% was obtained as the ratio of ethanol to THF was 7:3. The macroscopic reaction kinetic study indicated that THF can protect EMF from easy degradation to EL. Moreover, the reusability and the characterization of USY verified the feasibility of USY as an efficient solid acid catalyst. In this study, density functional theory (DFT) calculations for the catalytic mechanism and solvent effect at the molecular scale were performed for the first time. The extra-framework aluminum species (EFAL), in which Al 3+ played an essential role in the reaction as the preferred EFAL species, and THF can reduce the energy barrier of USY-catalyzed glucose isomerization. Meanwhile, the inhibitory effect of THF on EMF alcoholysis was explored via the frontier molecular orbital theory. The results showed that THF increased the LUMO energy of EMF compared with ethanol and γ-valerolactone, which decreased its susceptibility to nucleophilic attack and reduced the adverse alcoholysis of EMF and humins formation. This study provided an enlightening reference for the efficient synthesis of EMF from carbohydrates catalyzed by solid acid catalyst under solvent effect.